Implementation of Digital Fairy Tales in an Effort to Cultivate Character in Children Aged 5-6 Years - Khotimah, Mutiara Khusnul; Cholimah, Nur (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2025)
This study aimed to describe the implementation of digital fairy tales in an effort to instill characters in children aged 5-6 years. The method used in this study was descriptive of the type of case study research. The data sources taken included two teachers, one principal, and 10 children aged 5-6 years. Then, the techniques used in this study consist of observation, interviews, and documentation. Furthermore, the data obtained was analyzed using the stages of data reduction, data display, and drawing a conclusion. This study found that the implementation of digital fairy tales in an effort to build the character of children aged 5-6 years at school applied the strategy from Lickona. These strategies include moral knowing, which is applied by conveying understanding and comprehension of character; moral feeling, which is applied by building understanding and mindset in children; and moral action, which is applied by carrying out good character habits.